Pendidikan Islam, Tasawuf, dan Tantangan Era Society 5.0 - Fuady, Rifa Hazim Rustam (Bestari, 2021)
Advances in information and communication technology in the industrial revolution era demand a culture of society that integrates technology in their lives to become a super smart society in the era of society 5.0. Islamic education is certainly experiencing the impact of new problems that will be faced and the need for reconstruction in order to produce a generation that is not only able to adapt to technology but can realize an advanced Islamic civilization. This paper aims to reveal the challenges of the era of society that will be faced by Islamic education and the relevance of Islamic education according to Sufism in responding to these challenges. This paper is a library research that uses qualitative-descriptive-analytic research methods. The results of this study indicate that the opposition to Islamic education in the era of society 5.0 is (a) it is necessary to form education that produces a generation that understands universal Islam which makes Islam not only made into law but also a way of life (b) it is necessary to erode the dichotomy of science in Islamic education by open a good integration between the two (c) Islamic education must be able to fortify the progress of science and technology with Islamic values ​​so as not to get out of the way of benefit. All of these problems are relevant to the use of the Sufism approach in Islamic education.